INTERNALIZATION OF THE VALUE OF MAKKULIWA SMART INDONESIA CARD RECIPIENTS AT THE UNIVERSITY OF WEST SULAWESI: AN ECONOMIC VERSUS INVESTMENT PERSPECTIVE ON STUDENT PARENTS - Indra Basir; Yudia Fatih Afandi Putri; Puspa Alma; Muhammad Ariyanto Yahya; M. Rifqi Auliya; Hendri Pradana Montoya (Jurnal Ekonomi, 2023)
The Indonesia Smart College Card (KIP-Kuliah) is useful for young people who want to continue their studies in college, as a government effort to increase access to education for students from underprivileged but outstanding backgrounds. The purpose of this research is to reveal the perspective of parents of KIP-College recipient students at Unsulbar in viewing KIP-College from an economic or investment perspective by internalizing the value of the makkuliwa tradition in Mandar land. This research uses qualitative methods through a phenomenological approach. Data collection techniques through observation, literature studies and interviews (in-depth interviews), determining informants using purposive sampling method. Data processing techniques using Nvivo12 plus. Interactive model of analysis technique. The results of this research show that parents of students predominantly view KIP-College as an economic perspective that becomes additional family income. Meanwhile, the view of the investment perspective from the parents of students in managing KIP-College funds is still very minimal. Therefore, building parents' perspectives through the application of the value of the makkuliwa tradition can have a domino effect, namely increasing the enthusiasm of students in pursuing education so that they have achievements and have greater opportunities in achieving their careers in the future.